Socio-economic impacts of the recent bio-invasion of Callinectus sapidus on small-scale artisanal fishing in southern Italy and Portugal - Nardelli, Ludovica; Fucilli, Vincenzo; Pinto, Hugo; Elston, Jennifer Nicole; Carignani, Annalisa; Petrontino, Alessandro; Bozzo, Francesco; Frem, Michel (Frontiers in Marine Science, 2024)
Introduction The recent and growing bio-invasion of the Callinectes sapidus (known as blue crab) is causing damages in the European aquatic ecosystems, and affecting the livelihoods of the fishermen. In this context, this study explores the socio-economic impacts of this bio-invasion on small-scale artisanal fishermen in the Apulia (southern Italy) and Algarve (southern Portugal) regions, analyzing their perceptions and highlighting the repercussions of this bio-invasion on their livelihoods. Methods For this purpose, we carried out a field survey with representative small-scale artisanal fishermen based on the “Socio-economic Impact Classification of Alien Taxa” (SEICAT) approach by means of an “Exploratory Factor Analysis” (EFA), and a “Hierarchical Analysis and K-means Cluster Analysis”. Results and discussion The findings reveal that the two study areas, Apulia and Algarve, exhibit markedly different perceptions of the impact of the blue crab invasion on the well-being and activity of fishermen. In Apulia, the invasion has led to extensive damage to fishing nets, physical harm, a decline in other commercial species, reduced catch quantities, increased working hours, higher costs, and lower incomes. Conversely, in the Algarve, while net damage is less severe, the primary concerns are physical harm, increased working hours, higher costs, and reduced income. Consequently, this research provides an empirical basis for the adoption of management measures and interventions to mitigate the socioeconomic impacts of the blue crab on the fishing community and local economy, thereby contributing to the well-being of both individuals and the marine ecosystem.